Kemampuan Speaking Mahasiswa Semester 4 Jurusan Sastra Inggris Universitas Putera Batam - Fasaaro Hulu; Ambalegin Ambalegin (Prosiding, 2018)
This research is aimed to analyse students' speaking ability in English. and using speech measurement capabilities based on three aspects according to the theory of Luis V. (2010), as; refers on grammar (grammar), proper and correct vocabulary, pronunciation (pronunciation). The test of the ability to speak through an explanation on the image displayed in front of the class, majoring in English Literature, Putera Batam University, which consists of 53 students who participated as participants. In obtaining the research data, the researchers use the method of observation, recording activities and interview (interview) almost all the students who present in the class. And the data had been analyzed by grouping, classifying, comparing the data and distinguish data base on the 5 (five) categories, consisting of categories; unsatisfactory category (US), fair category (F), good category (G), excellent category (VG) and the excellent category (E). And the data analyzed by category that displays through tables and detail elaboration by using text. The results were found and spread on the average test of 53 students obtained is 63.67. Found 10 students categorize as US, 26 students categorize as F, 15 students categorize as G and 2 students categorize as E. So, the over all average students’score is 63.67, so can be concluded that the students’ ability in speaking English is categorized as fair category.